"It's easier to stick a tube in": a qualitative study to understand clinicians' individual decisions to place urinary catheters in acute medical care. Issue 7 (11th June 2015) - Murphy, Catherine; Prieto, Jacqui; Fader, Mandy
Abstract : Background: Indwelling urinary catheters (IUCs) placed in acute care are a leading cause of healthcare-associated urinary tract infection. Despite initiatives to minimise the placement of IUCs, levels of inappropriate use are still considered unacceptable. IUC practice is difficult to change, and factors influencing clinicians' decisions need to be better understood. Objective: To explore why clinicians decide to place IUCs in acute medical care. Methods: We conducted a qualitative study in the emergency department and acute medical wards of a 1200+ bed hospital, undertaking 30 retrospective think aloud and 20 semistructured interviews with nurses and physicians who made the decision to place an IUC. A purposive sample and thematic analysis were used. Results: Opinions on when an IUC was warranted varied considerably. Inconsistency in decision-making was caused by differing beliefs on when an IUC was appropriate for each clinical indication. Numerous patient and non-patient factors, including clinical setting, resources, patient age and gender and staff workload, also impacted on each decision. Assessing when the benefit of an IUC outweighed the risk could be problematic due to conflicting goals. Conclusions: These findings help to explain why clinicians sometimes deviate from IUC best practice guidance and resist interventions to modify practice. In order to engage nurses and physicians in change, interventions to reduce IUC use should acknowledge and respond to the complexity and lack of clarity often faced by clinicians making the decision to place an IUC. However, it is equally important that inconsistencies in IUC-related beliefs are recognised, investigated and, where appropriate, challenged.